Efficacy of different biopesticides against sucking pests infesting okra, Abelmoschus esculentus L. (Moench) - Kekan, Akshay M; Gurav, S S; Sanap, P B; Panchare, Anand M (Indian Journal of Plant Protection, 2023)
In order to examine the efficacy of different biopesticides against sucking pests of okra viz., leaf hopper, aphid and whitefly, a field study was taken at Central Experimental Station Wakawali, Maharashtra, India during kharif 2019-2020. The results revealed that azadirachtin 1% EC @ 0.003 per cent was the best treatment, recorded with minimum (3.07) mean leaf hopper population per three leaves and was followed by the treatment Lecanicillium lecanii @ 5gm/l (3.48 leaf hoppers/three leaves). For aphid Lecanicillium lecanii @ 5gm/l was the best treatment which was recorded minimum (6.28) mean aphid population per three leaves and was followed by treatment Azadirachtin 1% EC @ 0.003 per cent (6.65 aphids/three leaves). Lecanicillium lecanii @ 5gm/lit was the best treatment against whitefly as it was recorded with minimum (2.58) mean whitefly population per three leaves and was followed by azadirachtin 1% EC @ 0.003 per cent (2.72 whiteflies) and Beauveria bassiana @ 5g/l (3.17 whiteflies).